Prevalence and risk factors of uterine prolapse in Achham district, Nepal. - Bogati,Namita Kumari (2019)
ABSTRACT: Background: Uterine Prolapse is one of the hidden morbidities that do not lead to death but women suffer from severe lifelong disabilities. Due to different underlying factors, still the prevalence of UP still ranges from 10 to 40 percent among women in Nepal. Therefore, the main aim of the study was to identify the prevalence, associated risk factors and women's experience regarding uterine prolapse. Methods: The community based descriptive cross sectional study was conducted among 300 married women of age above 18 years who have/had suffered from uterine prolapse at four villages of Kamal Bazar municipality, Achham district. Results: The prevalence of uterine prolapse was 33.7%. In multivariate analysis, participants with age group The participants of age 20-30 years were 41 times more likely to suffer from uterine prolapse than old aged participants of age group 50-60 years {aOR 41.86 (95% CI; 14.31-122.45)}, were 7 times more likely to have not attended health facilities for ANC/PNC {aOR 7.10 (95%CI; 3.53-14.26)}, were less likely to have institutional delivery {aOR 0.13 (95% CI;0.05-0.31)} were 3 times more likely to have high BMI {aOR 3.97 (95% CI; 1.81-8.71)}. Conclusion: Thus, the participants who hadn't attained ANC/PNC checkups, had conducted the home delivery and the participants with high BMI had suffered from uterine prolapse. Keywords: Uterine prolapse, Prevalence, Risk factors, Women's experience